Acute promyelocytic leukemia can be fully treated on an outpatient basis: a single institution experience - Danae García-Vélez; Moisés Manuel Gallardo-Pérez; Gloria Erendy Cruz-Pérez; Miranda Melgar-de-la-Paz; Luis Enrique Hamilton-Avilés; Paola Negrete-Rodríguez; Olivia Lira-Lara; Max Robles-Nasta; Juan Carlos Olivares-Gazca; Solón Javier Garcés-Eisele; Guillermo J. Ruiz-Delgado; Guillermo Jose Ruiz-Argüelles (Hematology)
The objective of this study is to explore the possibility of treating APL patients fully as outpatients. A total of 21 consecutive APL patients were identified over 30 years in the Centro de Hematología y Medicina Interna de Puebla, at Clínica Ruiz, but only 17 were studied, treated as outpatients, and followed for at least 1 month; they were observed for median of 95 months, their median age was 27 years and all were treated with ATRA, prednisone, and adriamycin as outpatients. Treatment was completed on an outpatient basis in 15/17 cases. Molecular remission was achieved in 16/17 patients. The median follow-up was 95 months (IQR 19 - 360). The median OS and LFS were not reached, and the 12-month LFS was 94%. We have confirmed that APL can be treated entirely on an outpatient basis: this observation is of utmost relevance in a resource-limited setting, such as those prevailing in low- and middle-income countries.